Optimization of a novel nitric oxide sensor using a latex rubber matrix - Herculano, Rondinelli Donizetti; Brunello, C. A.; Graeff, Carlos Frederico de Oliveira [UNESP] (My University, 2007)
This study present a novel NO sensor made of a spin trap (iron(II)-diethyldithiocarbamate complex, FeDETC) incorporated in a latex rubber matrix and works as a trap for NO, which is detectable by Electron Paramagnetic Resonance (EPR). We explored the optimization of our sensors changing systematically two fabrication parameters: the latex rubber matrix temperature of polymerization and FeDETC concentration inside the matrix. The sensor was prepared in four different temperatures: 4, 10, 20 and 40°C. The FeDETC concentration was also varied from 0.975 to 14.8 mM. We observed a variation of the EPR signals from the sensors prepared at different conditions. We found a high stability of the EPR response from our sensor, 40 days at RT. The best sensor was made with a latex rubber matrix polymerized at 10°C and with a FeDETC concentration of 14.8 mM. In vivo tests show good biocompatibility of our sensor. © 2007 Asian Network for Scientific Information.
Keywords: FeDETC; Latex rubber matrix; Nitric oxide; Optimization; Sensor